Computational literary studies and pedagogical practice - Flüh, Marie (Kalbotyra, 2025)
This article presents a teaching concept for the professionalization of prospective teachers. The concept is focused on the synchronization of basic digital skills in dealing with different methods of computational text analysis – which also includes literary studies-oriented corpus analyses – with the development of didactic skills. After a brief introduction, the first part of the article highlights the motivation and relevance of bridging the gap between digital humanities and teacher training. The second part focuses on conceptual foundations, areas of knowledge, and the rough outline of the seminar “Digital Literary Studies and Literary Didactics” (held in the Winter semester of Study year 2023/24 and the Winter semester of 2024/25 at the Institute of German Studies at the University of Hamburg) with special consideration of the session on corpus analysis. Finally, the results, opportunities and limitations of the teaching concept are examined.